An Earth Observation Data Ecosystem to Enhance Environmental Monitoring and Society's Resilience in Cyprus and the EMMENA Region - Neophytides, Stelios; Mavrovouniotis, Michalis; Christoforou, Nikos; Drivas, Thanassis; Eliades, Marinos; Papoutsa, Christiana; Mamouri, Rodanthi-Elisavet; Fragkos, Konstantinos; Ene, Dragos; Bachofer, Felix; Krauss, Thomas; Schwarz, Egbert; et al. (My University, 2024)
The rapid growth of Earth Observation (EO) and Remote Sensing (RS) data has underscored the critical need for identifying optimal solutions to effectively manage EO Big Data. This entails simplifying data sharing and facilitating adaptation across multidisciplinary applications to better serve the research community. Various architectures and structures have been developed to manage and deploy these data in an analysis-ready format. In this study, we provide a concise overview of an advanced EO Big Data infrastructure located in Limassol, Cyprus, comprising diverse data sources acquired from an acquisition station, an atmospheric ground base station, and various living labs. Additionally, we present the EO data ecosystem of Cyprus that is specifically designed to efficiently store the aforementioned data.
Keywords: Earth Observation; Remote Sensing; Big Earth Data; Analysis Ready Data; Data Cube